An Overview of BCC Climate System Model Development and Application for Climate Change Studies - 吴统文 宋连春 李伟平 王在志 张华 辛晓歌 张艳武 张莉 李江龙 吴方华 刘一鸣 张芳 史学丽 储敏 张洁 房永杰 汪方 路屹雄 刘向文 魏敏 刘茜霞 周文艳 董敏 赵其庚 季劲钧 Laurent LI 周明煜 (Acta meteorologica Sinica, 2014)
This paper reviews recent progress in the development of the Beijing Climate Center Climate System Model （BCC_CSM） and its four component models （atmosphere, land surface, ocean, and sea ice）. Two recent versions are described： BCC_CSMI.1 with coarse resolution （approximately 2.8125°× 2.8125°） and BCC_CSMI.I（m） with moderate resolution （approximately 1.125°×1.125°）. Both versions are fully cou- pled climate-carbon cycle models that simulate the global terrestrial and oceanic carbon cycles and include dynamic vegetation. Both models well simulate the concentration and temporal evolution of atmospheric CO2 during the 20th century with anthropogenic CO2 emissions prescribed. Simulations using these two versions of the BCC_CSM model have been contributed to the Coupled Model Intercomparison Project phase five （CMIP5） in support of the Intergovernmental Panel on Climate Change （1PCC） Fifth Assessment Report （AR5）. These simulations are available for use by both national and international communities for investigating global climate change and for future climate projections. Simulations of the 20th century climate using BCC-CSMI.1 and BCC_CSMI.I（m） are presented and validated, with particular focus on the spatial pattern and seasonal evolution of precipitation and surface air temperature on global and continental scales. Simulations of climate during the last millennium and projections of climate change during the next century are also presented and discussed. Both BCC_CSMI.1 and BCC_CSMI.I（m） perform well when compared with other CMIP5 models. Preliminary analyses in- dicate that the higher resolution in BCC CSMI.I（m） improves the simulation of mean climate relative to BCC_CSMI.1, particularly on regional scales.